Prevention of acute knee injuries in adolescent female football players: cluster randomised controlled trial. (3rd May 2012) - Waldén, Markus; Atroshi, Isam; Magnusson, Henrik; Wagner, Philippe; Hägglund, Martin
Abstract : Objective To evaluate the effectiveness of neuromuscular training in reducing the rate of acute knee injury in adolescent female football players. Design Stratified cluster randomised controlled trial with clubs as the unit of randomisation. Setting 230 Swedish football clubs (121 in the intervention group, 109 in the control group) were followed for one season (2009, seven months). Participants 4564 players aged 12-17 years (2479 in the intervention group, 2085 in the control group) completed the study. Intervention 15 minute neuromuscular warm-up programme (targeting core stability, balance, and proper knee alignment) to be carried out twice a week throughout the season. Main outcome measures The primary outcome was rate of anterior cruciate ligament injury; secondary outcomes were rates of severe knee injury (>4 weeks' absence) and any acute knee injury. Results Seven players (0.28%) in the intervention group, and 14 (0.67%) in the control group had an anterior cruciate ligament injury. By Cox regression analysis according to intention to treat, a 64% reduction in the rate of anterior cruciate ligament injury was seen in the intervention group (rate ratio 0.36, 95% confidence interval 0.15 to 0.85). The absolute rate difference was −0.07 (95% confidence interval −0.13 to 0.001) per 1000 playing hours in favour of the intervention group. No significant rate reductions were seen for secondary outcomes. Conclusions A neuromuscular warm-up programme significantly reduced the rate of anterior cruciate ligament injury in adolescent female football players. However, the absolute rate difference did not reach statistical significance, possibly owing to the small number of events. Trial registration Clinical trials NCT00894595 .